IMPACT OF SELF -EFFICACY ON ENTREPRENEURIAL INTENTION OF UNIVERSITY GRADUATES IN OGUN STATE, NIGERIA (Journal of Technology and Operations Management, 2023)
This study examines the impact of self-efficacy on the entrepreneurial intentions of university graduates in Ogun State, Nigeria. The specific objectives of the study were to: determine the impact of vicarious experience and social persuasion on entrepreneurial intention. The study was exploratory and used cross-sectional analysis that allows data from the population using a survey research design. The study population comprises 71,173 university undergraduates in the three senatorial districts in Ogun State, Nigeria, during the 2019/2020 and 2020/2021 academic sessions. The study collected data by distributing 398 questionnaires to university students in Ogun State, Nigeria, but analysed 318 questionnaires retrieved and suitable for this study. The data analysis encompassed the utilisation of both descriptive and inferential statistics. The results of the study indicate that vicarious experience (R = 0.398, R2 =0.158, P < 0.05), and social persuasion (R = 0.279, R2 =0.078, P < 0.05) exert a statistically significant and positive influence on the entrepreneurial intentions of university students. The study concluded that there is a statistically significant association between self-efficacy and entrepreneurial intentions among university students in Ogun State, Nigeria. This study enhances the existing knowledge by elucidating the specific elements of vicarious experience and social persuasion as major factors in the connection between self-efficacy and entrepreneurial intentions among university graduates. The study recommended that policymakers and educators should promote positive role models, provide opportunities for observation and learning, and create a supportive environment for entrepreneurship to encourage more university graduates to pursue entrepreneurial opportunities.